2022
DOI: 10.1002/oby.23386
|View full text |Cite
|
Sign up to set email alerts
|

Examination of serum metabolome altered by cigarette smoking identifies novel metabolites mediating smoking‐BMI association

Abstract: Objective The authors hypothesize that an untargeted metabolomics study will identify novel mechanisms underlying smoking‐associated weight loss. Methods This study performed cross‐sectional analyses among 1,252 participants in the Bogalusa Heart Study and assessed 1,202 plasma metabolites for mediation effects on smoking‐BMI associations. Significant metabolites were tested for associations with smoking genetic risk scores among a subset of participants (n = 654) with available genomic data, followed by direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…No features were statistically different among the groups, suggesting the application of metabolomics in tobacco cessation studies. A larger study of 1252 participants incorporating the assessment of smoking-related weight loss where eight plasma xenobiotics were associated with former smoking and 22 xenobiotics and 94 endogenous metabolites were significantly associated with current smoking, including α -ketobutyrate, homoarginine, β -cryptoxanthin, 1-linoleoyl-GPE (18:2), 1-Palmitoyl-GPE (16:0), 1-Stearoyl-2-arachidonoyl-GPE (18:0/20:40 and 2 sphingomyelins [ 95 ].…”
Section: Omics Methods and Examples Of Applications ( Table...mentioning
confidence: 99%
“…No features were statistically different among the groups, suggesting the application of metabolomics in tobacco cessation studies. A larger study of 1252 participants incorporating the assessment of smoking-related weight loss where eight plasma xenobiotics were associated with former smoking and 22 xenobiotics and 94 endogenous metabolites were significantly associated with current smoking, including α -ketobutyrate, homoarginine, β -cryptoxanthin, 1-linoleoyl-GPE (18:2), 1-Palmitoyl-GPE (16:0), 1-Stearoyl-2-arachidonoyl-GPE (18:0/20:40 and 2 sphingomyelins [ 95 ].…”
Section: Omics Methods and Examples Of Applications ( Table...mentioning
confidence: 99%
“…Some examples of environmental factors influencing the metabolome include s ing and diet. Cigarette smoking has been found to alter the metabolome and metab associated, with smoking having also been found to be associated with body mass i (BMI) [19]. Zhang et al discovered that a total of 168 metabolites were altered d smoking, and 40 were metabolites that mediate the smoking-BMI association [19] known metabolites belonged to compound groups, lipids, xenobiotics, amino acids more [19].…”
Section: Patient Selectionmentioning
confidence: 99%
“…Cigarette smoking has been found to alter the metabolome and metab associated, with smoking having also been found to be associated with body mass i (BMI) [19]. Zhang et al discovered that a total of 168 metabolites were altered d smoking, and 40 were metabolites that mediate the smoking-BMI association [19] known metabolites belonged to compound groups, lipids, xenobiotics, amino acids more [19]. A small difference in diet, such as an increased consumption of whole whe white bread, can result in differences in betaine and cytosine levels [20].…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed increased bile acid metabolites, especially taurodeoxycholic acid in the colon of mice after smoke exposure (Bai et al, 2022). In addition, the serum metabolome of smoking patients has been identified to differ from that of non-smoking individuals (Xu et al, 2013;Zhang et al, 2022). For instance, Xu et al indicated that compared with former and non-smokers, in male current smokers, the concentrations of four unsaturated diacyl-phosphatidylcholines (PCs) and five amino acids (arginine, aspartate, glutamate, ornithine and serine) were increased, while three saturated diacyl-PCs, one lysoPC and four acyl-alkyl-PCs, as well as kynurenine showed lower content.…”
Section: Introductionmentioning
confidence: 99%